Comparison of the aneugenic properties of nocodazole, paclitaxel and griseofulvin in vitro. Centrosome defects and alterations in protein expression profiles. Issue 9 (19th March 2012) - Zacharaki, Polyxeni; Stephanou, Georgia; Demopoulos, Nikos A.
ABSTRACT: We have comparatively investigated the aneugenic activity of two anticancer drugs, nocodazole (NOC) and paclitaxel (PTX), and the antifungal griseofulvin with promising role in cancer treatment (GF), which affect microtubule dynamics in different ways. The comparison was achieved in HFFF2 human fibroblasts, MCF‐7 human breast cancer cells and C2C12 mouse myoblasts, and focused on three issues: (i) induction of chromosome delay by estimation of MN frequency using CREST analysis; (ii) disturbance of spindle organization with Aurora‐A/ β ‐tubulin immunofluorescence; and (iii) alterations in the expression of Aurora‐A, β ‐ and γ ‐tubulin by western blotting. They induced chromosome delay, provoked metaphase arrest and promoted microtubule disorganization, reflecting their common characteristic of generating aneuploidy. In particular, NOC induced mainly monopolar metaphases, although PTX induced only multipolar metaphases. GF generated different types of abnormal metaphases, exhibiting cell specificity. Additionally, NOC decreased the expression of Aurora‐A and β ‐tubulin, while the opposite held true for PTX and GF. γ ‐Tubulin expression was not modulated owing to NOC treatment, whereas PTX and GF increased γ ‐tubulin expression. Our findings throw a light on the manifestation of the aneugenicity of the studied compounds through centrosome proliferation/separation and protein expression, reflecting their different effects on microtubule dynamics. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : Nocodazole, paclitaxel and the antifungal griseofulvin, with a promising role in cancer treatment, affect microtubule dynamics by different ways. To compare their aneugenic properties we studied: (i) MN induction using CREST analysis, (ii) disturbance of mitotic spindle organization by immunofluorescence, and (iii) alterations in the expression of chromosome segregation regulating protein. We found that the generation of different types of abnormal metaphases dowing to centrosome deffects, as well as the alteration in the expression of proteins regulating chromosome segregation, was dependent on the drug and the cell line treated, reflecting their different effects on microtubule dynamics.